Formation of wakes by chiral conducting cosmic strings - Abdalla, MCB; Bytsenko, A. A.; Guimaraes, MEX (World Scientific Publ Co Pte Ltd, 2004)
Chiral cosmic strings are naturally produced at the end of D-term inflation and they present very interesting cosmological consequences. In this work, we investigate the formation and evolution of wakes by a chiral string. We show that, for cold dark matter, the mechanism of forming wakes by a chiral string is similar to the mechanism by an ordinary string.
Keywords: topological defects; formation of large scale structure